2022
DOI: 10.3390/polym14224976
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Response to the Surface Aging of PLA Matrices Loaded with Active Compounds

Abstract: The use of active components in biomaterials improves the properties of existing ones and makes it possible to obtain new devices with antibacterial properties that prevent infections after implantation, thus guaranteeing the success of the implant. In this work, cetyltrimethylammonium bromide (CTAB) and magnesium particles were incorporated into polylactic acid (PLA) films to assess the extent to which progressive aging of the new surfaces resists bacterial colonization processes. For this purpose, the films’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
2
1
Order By: Relevance
“… Fernández-Grajera et al (2022) evaluated the influence of aging on microbial adhesion of PLA incorporated with cetyltrimethylammonium bromide (CTAB) and magnesium and observed that aging increased microbial adhesion on the surface after 3 months (p > 0.05) and further reported that there was no influence of aging on the hydrophobicity of the material ( Fernández-Grajera et al, 2022 ), which differs from this study since aging reduced the control group's CA and surface roughness. Despite not having performed PP techniques, the results differ from those found in this study in which the adhesion of C. albicans (p = 0.563) and S. mutans (p = 0.813) did not change as a function of 6-month aging.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“… Fernández-Grajera et al (2022) evaluated the influence of aging on microbial adhesion of PLA incorporated with cetyltrimethylammonium bromide (CTAB) and magnesium and observed that aging increased microbial adhesion on the surface after 3 months (p > 0.05) and further reported that there was no influence of aging on the hydrophobicity of the material ( Fernández-Grajera et al, 2022 ), which differs from this study since aging reduced the control group's CA and surface roughness. Despite not having performed PP techniques, the results differ from those found in this study in which the adhesion of C. albicans (p = 0.563) and S. mutans (p = 0.813) did not change as a function of 6-month aging.…”
Section: Discussioncontrasting
confidence: 54%
“…Annealing the sample is a technique for performing thermal PP, which reduces the residual thermal stresses between layers from the printing process and promotes the viscoelastic relaxation of the polymer with a consequent filling of the voids between layers and pores with reduced surface roughness ( Gao et al, 2020 , Singh et al, 2019 ). In this study, thermal PP did not reduce surface roughness statistically significantly, since this method increases the degree of crystallinity when performed at temperatures above the glass transition temperature (Tg) ranging from 55 to 65 °C, which can alter the mechanical properties such as flexural strength and roughness ( Fernández-Grajera et al, 2022 , Meng et al, 2012 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation